Elephantine, Ägypten. Projekt Lebenswirklichkeiten (Realities of Life) - Sigl, Johanna; Kopp, Peter (e-Forschungsberichte des DAI, 2017)
Since 1969 the excavations of the DAI and its cooperative partner, the Swiss Institute in Cairo, on Elephantine Island, have concentrated mainly on the building history of the settlement as well as the study of the temples of Khnum and Satet and their surroundings, from the Early Dynastic Period approx. 4th mil. BC) until the Late Roman Period (until 642 AD in Egypt). The project “Realities of Life”, initiated in autumn 2013, now redirects the focus of the work of the DAI onto the living conditions and daily life of the people inhabiting the Middle Kingdom town (ca. 1980–1760 BC). These scientific aims will be pursued with a strong reliance on archaeometric methods and local scientific cooperation, which could be set up during the initial phase of the project.